Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov - Oliveira, Jadson J.S.; Vargas-isla, Ruby; Cabral, Tiara Sousa; Doriane, Picanço Rodrigues; Ishikawa, Noemia Kazue (Mycological Progress, 2019)
Omphalotaceae is the family of widely distributed and morphologically diverse marasmioid and gymnopoid agaric genera. Phylogenetic studies have included the family in Agaricales, grouping many traditionally and recently described genera of saprotrophic or parasitic mushroom-producing fungi. However, some genera in Omphalotaceae have not reached a stable concept that reflects monophyletic groups with identifiable morphological circumscription. This is the case of Gymnopus and Marasmiellus, which have been the target of two opposing views: (1) a more inclusive Gymnopus encompassing Marasmiellus, or (2) a more restricted Gymnopus (s. str.) while Marasmiellus remains a distict genus; both genera still await a more conclusive phylogenetic hypothesis coupled with morphological recognition. Furthermore, some new genera or undefined clades need more study. In the present paper, a phylogenetic study was conducted based on nrITS and nrLSU in single and multilocus analyses including members of the Omphalotaceae, more specifically of the genera belonging to the /letinuloid clade. The resulting trees support the view of a more restricted Gymnopus and a distinct Marasmiellus based on monophyletic and strongly supported clades on which their morphological circumscriptions and taxonomic treatments are proposed herein. The results also provide evidence for the description of two new genera: Paragymnopus and Pusillomyces. Pusillomyces manuripioides sp. nov. (type species of the genus) is described with morphological description, taxonomic and ecological remarks, and illustrations. © 2019, German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature.